2020
DOI: 10.1101/2020.12.15.422870
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pupil-based states of brain integration across cognitive states

Abstract: Arousal is a potent mechanism that provides the brain with functional flexibility and adaptability to external conditions. Within the wake state, arousal levels driven by activity in the neuromodulatory systems are related to specific signatures of neural activation and brain synchrony. However, direct evidence is still lacking on the varying effects of arousal on macroscopic brain characteristics and across a variety of cognitive states in humans. Using a concurrent fMRI-pupillometry approach, we used pupil s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Combining whole-brain fMRI with real-time pupillometry provides a non-invasive mapping scheme to identify pupil-fMRI relationships across different species. Existing human fMRI studies with pupillometry have revealed pupil dynamic changes associated with the activation of subcortical brain nuclei along the ascending arousal network, as well as the salience network including the cingulate cortex and insula 32,[41][42][43][44][45][46][47][48][49] . Interestingly, opposite arousal correlation features between eye movements and resting-state fMRI have been revealed between the cortex and subcortical nuclei in both non-human primates and rodent brains [50][51][52] .…”
Section: Introductionmentioning
confidence: 99%
“…Combining whole-brain fMRI with real-time pupillometry provides a non-invasive mapping scheme to identify pupil-fMRI relationships across different species. Existing human fMRI studies with pupillometry have revealed pupil dynamic changes associated with the activation of subcortical brain nuclei along the ascending arousal network, as well as the salience network including the cingulate cortex and insula 32,[41][42][43][44][45][46][47][48][49] . Interestingly, opposite arousal correlation features between eye movements and resting-state fMRI have been revealed between the cortex and subcortical nuclei in both non-human primates and rodent brains [50][51][52] .…”
Section: Introductionmentioning
confidence: 99%
“…Resting state fMRI (rs-fMRI) studies have uncovered global pupil-fMRI correlation patterns in human brains as well as revealed that the pupil dynamics-fMRI relationship changed under different lighting conditions or when subjects engaged in mental imagery (22,26). The dynamic functional connectivity changes detected by fMRI, possibly modulated by the interplay of cholinergic and noradrenergic systems (41), are also reflected by pupil dynamics both at rest (42) and in task conditions (43). Furthermore, rs-fMRI has been used to display a differential correlation pattern with brainstem noradrenergic nuclei, e.g., A5 cell group, depending on the cortical crossfrequency coupling state in the animal model (23).…”
Section: Introductionmentioning
confidence: 99%